Influence of the holm oak soda pulping conditions on the properties of the resulting paper sheets. (Bioresource technology, 2008)
This paper reports on the influence of independent variables in the pulping of holm oak wood [viz. temperature (135-195 degrees C), cooking time (30-90 min) and soda concentration (10-20%)] on the properties of the resulting paper sheets. By using a central composite factorial design and a fuzzy neural model, equations relating each dependent variable to the different independent variables were derived that reproduced the experimental results for the dependent variables with errors less than 14%. Using a soda concentration of 17.5% at 195 degrees C for 30 min, it is possible to reduce the working capital (cost of chemical) and the capital investment, because it is operated with smaller values of the soda concentration and cooking time that maximum considered (20% of soda concentration and 90 min). The pulp yield thus obtained differed by less than 31.3% from the highest possible value; also, the resulting pulp and paper sheets had acceptable properties that differed by less than 21.10% from their optimum values.

Influence of the holm oak soda pulping conditions on the properties of the resulting paper sheets. - Alaejos, Joaquín; López, Francisco; Pérez, Antonio; Rodríguez, Alejandro; Jiménez, Luis (Bioresource technology, 2008)
This paper reports on the influence of independent variables in the pulping of holm oak wood [viz. temperature (135-195 degrees C), cooking time (30-90 min) and soda concentration (10-20%)] on the properties of the resulting paper sheets. By using a central composite factorial design and a fuzzy neural model, equations relating each dependent variable to the different independent variables were derived that reproduced the experimental results for the dependent variables with errors less than 14%. Using a soda concentration of 17.5% at 195 degrees C for 30 min, it is possible to reduce the working capital (cost of chemical) and the capital investment, because it is operated with smaller values of the soda concentration and cooking time that maximum considered (20% of soda concentration and 90 min). The pulp yield thus obtained differed by less than 31.3% from the highest possible value; also, the resulting pulp and paper sheets had acceptable properties that differed by less than 21.10% from their optimum values.
The following values have no corresponding Zotero field: accession-num: 18226524
Keywords: Paper; Textile Industry; Wood